1993
DOI: 10.1021/ac00070a002
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic wave microsensors. Part II

Abstract: coustic wave microsensors are a satile class of sensor with y applications. Although origially regarded as mass detectors, hese sensors can also measure a ion via mass sensitivity. focus on sensing i or behavior in the liquid ph e will begin Part II with a di , -Acoustic devices are usually converted to chemical sensors by the application of a chemically selective layer (1). Polymer materials have been used in organic vapor sensing applications because vapor sorption in rubbery polymers is rapid and reversible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 51 publications
(94 reference statements)
1
62
0
Order By: Relevance
“…The results of this analysis demonstrate the potential of the SAW instrument for selective measurement of perchloroethylene among a library set of common vapors and are consistent with more exhaustive studies in which the capabilities of SAW sensor arrays for mixture analysis were characterized. (17,(26)(27)(28)(29)(30)(31)(32)(33)37) The calibration protocols employed for the field study were simplified compared with those used in the laboratory evaluation in order to more accurately reflect the way the instruments would likely be used in practice. The portable GC was pre-and postcalibrated on site using three spiked breath standards having concentrations determined immediately prior to the study using the laboratory reference GC.…”
Section: Field Evaluation Of Saw Microsensor Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this analysis demonstrate the potential of the SAW instrument for selective measurement of perchloroethylene among a library set of common vapors and are consistent with more exhaustive studies in which the capabilities of SAW sensor arrays for mixture analysis were characterized. (17,(26)(27)(28)(29)(30)(31)(32)(33)37) The calibration protocols employed for the field study were simplified compared with those used in the laboratory evaluation in order to more accurately reflect the way the instruments would likely be used in practice. The portable GC was pre-and postcalibrated on site using three spiked breath standards having concentrations determined immediately prior to the study using the laboratory reference GC.…”
Section: Field Evaluation Of Saw Microsensor Arraymentioning
confidence: 99%
“…(26)(27)(28) Previous work has shown that an array of 3-6 SAW sensors coated with a set of polymers selected to provide a broad range of solubility interactions can yield characteristic response patterns allowing for the identification and quantification of a large number of individual vapors and components of simple mixtures. (17,(26)(27)(28)(29)(30)(31)(32)(33)37) Laboratory application of SAW-based instrumentation has been described for personal exposure monitoring and chemical protective clothing permeation testing. (26,34) The current study extends previous work that focused on the development and laboratory testing of SAW-based instrumentation for the analysis of organic vapors in breath.…”
Section: Introductionmentioning
confidence: 99%
“…The term is used here only in those material/sensor systems in which simply the mass change due to the sorption can cause a transduction effect [13]. Two types of sorption can be distinguished.…”
Section: Polymer Sorbent Coatingsmentioning
confidence: 99%
“…In the case of mass sensor application as the quartz microbalance, it is well known that the resonant frequency will change due to surface mass change, and the absolute frequency is proportional to the square of the operating frequency. 6,7 Therefore, using FBAR structures, with operation frequency in GHz range, can greatly improve the sensitivity of the device. In fact, chemical sensors based on FBARs have been experimentally investigated for low concentration detection, which showed much higher sensitivity and resolution comparable to quartz crystal microbalances.…”
Section: Introductionmentioning
confidence: 99%